Carbon Emissions and the Search for Renewable Energy Technology: Information and Communication Technology (ICT) Firms’ Environmental Responsibility - Kim, Hyunsoo; Jung, Hyun Ju; Lee, Chul Ho (Production and Operations Management, 2024)
The literature in sustainability has emphasized external pressures as a main driver of firms’ environmental responsibility. However, under similar external pressures, some firms search for environmental technology, while others do not. By focusing on information and communication technology (ICT) firms, we try to answer the question of when firms are motivated to search for renewable energy technology. Drawing on the framework of the behavioral theory of the firm, we propose that a mismatch between ICT firms’ CO 2 emissions performance and their aspiration to a certain level of emissions induce firms to evaluate their environmental performance status—whether they are aligned well with environmental requirements and their peer firms—and their technology status—whether they possess sufficient technologies to reduce emissions—which in turn affects their search for renewable energy technology. We corroborate our hypotheses using data on CO 2 emissions and renewable energy patents of U.S. ICT firms from 2010 to 2018. When we compare two groups of firms—one group whose emissions performance is poor and the other group whose emissions performance is good compared to their own past emissions—we find that the former is more likely to search for renewable energy technology compared to the latter. When we focus on each of the two groups, we find that firms decrease their search for renewable energy technology as the degree of poor emissions performance exacerbates (firms’ emissions increase above aspiration) or the degree of good emissions performance increases (firms’ emissions decrease below aspiration). Our findings have implications for public policy as well as firms’ environmentally sustainable operations.